Response of Cowpea (Vigna unguiculata L.) Varieties to Different Sowing Dates and Effect on Yield, Quality and Soil Fertility - SUTAR, V. K.; CHAVAN, L. S.; GAME, V. N. (Journal of the Indian Society of Coastal Agricultural Research, 2023)
An experiment was conducted on coastal lateritic soil of Konkan region to study the response of cowpea (Vigna unguiculata L.) varieties to different sowing dates and effect on yield, quality and soil fertility during Rabi-hot weather season 2011-12 at Agronomy department farm, College of Agriculture, Dapoli. The experiment was laid out in a split plot design with three replications. The main plot treatments were five sowing dates, namely, sowing of cowpea in 48th MW, 50th MW, 52nd MW, 2nd MW and 4th MW. The sub plot treatments comprised three cowpea varieties viz., Konkan Sadabahar, Konkan Safed and Phule Pandhari. Among the different sowing dates studied, 52nd MW recorded significantly higher yield, NPK and protein content over rest of the sowing dates. Among different cowpea varieties, Konkan safed recorded significantly higher yield, NPK and protein content over other two cowpea varieties. The soil available nitrogen, phosphorus and potassium after harvest of cowpea were not influenced significantly by both sowing dates and cowpea varieties.